Perlindungan Hukum Bagi Konsumen Kosmetik Atas Produk Parfum Isi Ulang - Renita Putri Kartika Reawaruw; Teng Berlianty; Sarah Selfina Kuahaty (PATTIMURA Law Study Review, 2023)
ABSTRACT: Currently, there are many business actors who get more profit by producing refill perfume containing hazardous substances that do not meet the requirements for circulation, so that Law No. 8 of 1999 was issued to provide legal protection for consumers. The purpose of this research was conducted to find out how the form of legal protection for cosmetic consumers for the distribution of perfume products containing dangerous substances and what form of legal protection for cosmetic perfume consumers who experience losses. The research method used is normative legal research method. The problem approach used is the statutory approach, the conceptual approach. The legal materials used are primary legal materials and secondary legal materials. Procedures and Collection of Legal Materials using the method of inventorying laws and regulations and Processing and Analysis of legal materials is carried out using qualitative analysis techniques to answer problems. Based on the results of the study it can be concluded: Forms of Legal Protection for Consumers of Cosmetics for the Circulation of Refillable Perfumes are divided into 2, namely, Forms of Preventive Legal Protection as a preventive measure for a person/group who wants to carry out activities or actions that are negative and Forms of Repressive Legal Protection are efforts settlement of the occurrence of violations with the aim of resolving disputes. Consumers who are disadvantaged as a result of using dangerous refill perfumes based on Law Number 8 of 1999 concerning Consumer Protection, there are two forms of legal remedies, namely through out-of-court dispute resolution which is carried out by the Consumer Dispute Settlement Agency and legal remedies through dispute resolution in court carried out with reference to to the provisions of the general court in force.